P ENGARUH CITRA MEREK, KEPERCAYAAN DAN E - WOM TERHADAP KEPUTUSAN PEMBELIAN PRODUK ORAL – B DI KOTA BATAM: bahasa indonesia - Christian Cendana; Yvonne Wangdra (LPPM Universitas Putera Batam, 2025)
This research aims to investigate whether brand image, trust, and electronic word of mouth (E-WOM) have an influence on purchase decisions for Oral-B toothbrush products in Batam City. The sample for this study consists of 383 respondents, selected using a purposive sampling technique. The criteria for respondents include individuals who have previously purchased Oral-B toothbrush products and who actively access social media platforms such as YouTube or Instagram. Data collection was conducted through a questionnaire distributed via Google Forms. The data analysis and testing were carried out using SPSS version 27. The stages of the research include descriptive data analysis, data quality testing, classical assumption testing, influence testing, and hypothesis testing. Based on the descriptive analysis, the responses indicated that the majority of respondents provided positive feedback on the statements presented in the questionnaire. The results of the regression analysis revealed that brand image, trust, and E-WOM collectively influence purchase decisions, with a contribution of 90.9%, while the remaining 9.1% is influenced by other variables not included in this study. Furthermore, hypothesis testing—both partial and simultaneous—demonstrated that brand image, trust, and E-WOM significantly affect consumers’ purchase decisions for Oral-B toothbrushes in Batam City. Keywords : Brand Image, Trust, E-WOM, Purchase Decisions